Massage therapy in the management of myogenic TMD: A pilot study - Capellini, Verena Kise; De Souza, Gisela Soares; De Faria, Cláudia Regina Sgobbi (FapUNIFESP (SciELO), 2006)
Introduction: The Temporomandibular disorder (TMD) is greatly prevalent in the population and can be associated with bruxism. This disorder produces several signs and symptoms. Among them, pain is one of the most important because it reduces life quality and productivity of people who have such disorder. The aim of this research was to study if massage causes pain relief and/or electromyographic (EMG) changes. Materials and methods: The subjects were chosen by a questionnaire and divided into 2 different groups. Their ages varied from 19 to 22 years. The experimental group consisted of 6 TMD patients, who were submitted to the massage treatment and 4 EMG-sessions (the 1 st EMG-session occurred before the treatment and the others in the 1 st, 15 th and 30 th days after the treatment). The control group consisted of 6 TMD patients, who were submitted to the same 4 EMG-sessions. While EMG activity was recorded, subjects were asked to keep mandibular rest position (MRP) and to perform maximal voluntary clenching (MVC). The treatment consisted of 15 massage-sessions on face and neck and in application of Visual Analogue Scale (VAS) for measuring pain level. The massage sessions had 30 minutes of duration and were performed daily. The EMG data were processed to obtain the Root Mean Square (RMS), which were normalized by MVC. Results: It was demonstrated that (1) RMS-MRP of the right masseter in experimental group at the 1 st EMG-session was higher than at the 2 nd EMG-session and (2) statistically significant reduction was found for VAS values after massage session. Conclusion: Unfortunately the sample is insufficient to draw any conclusions, therefore, more studies regarding the use of massage in the management of myogenic TMD are necessary.
Keywords: Bruxism; Electromyography; Massage; Pain; Temporomandibular disorder